ESTIMASI KONSENTRASI NO2 PERMUKAAN DARI TOTAL COLUMN NO2 SATELIT AURA-OMI DI CISARUA PERIODE 2017-2018 - Dewi Tamara Qothrunada; Virgianto, Rista Hernandi; Nugroho Dion Koestantio; Siti Najma Nindya Utami; Dhiyaul Qalbi Syofyan; Hendri Satria WD (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2019)
ABSTRACT AURA / OMI satellite data with a spatial resolution of 0.25 ÌŠ x 0.25 ÌŠ can be used to determine the concentration of pollutants in areas that have not been observed, one of them is NO2. NO2 total column concentrations derived from AURA / OMI satellite represent the density of pollutants vertically from the surface to the height of the troposphere, so it is necessary to calculate and estimate NO2 concentrations on the surface. The purpose of this study was to validate the surface NO2 concentrations estimation with the surface observation data at the Atmospheric Monitoring Post in Cisarua from January 2017 to December 2018. Estimation of surface NO2 concentration using AURA / OMI satellite was calculated by including vertical column density from CAMs model. The validation method used are correlation with significance test and error analysis using Root Mean Square Error (RMSE). Based on the calculation, the highest correlation coefficient obtained is 0.31 in March-April-May with significant test in the annual period and the March-April-May period. Error analysis results showed the lowest error value is in September-October-November while the highest value is in December-January-February. Keywords: NO2, AURA / OMI, CAMs, total column, estimation